Fanning Flames: A Review of 'The Adoring Audience' - Ludovica Price (The Comics Grid: Journal of Comics Scholarship, 2013)
A review of one of the seminal texts on fan culture, the review discusses the book's influence and relevance more than twenty years after its publication.